Solution to DC Optimal Power Flow Problems with Demand Response via Distributed Asynchronous Primal-Dual Algorithms. Issue 3 (1st May 2020) - Masuda, Eiji; Matsuda, Yusuke; Wakasa, Yuji; Adachi, Ryosuke
Abstract : As distributed energy resources increase, distributed optimization for power system operation and demand response (DR) have been intensively investigated in recent years. This paper presents a distributed solution for a DC optimal power flow problem with DR, which can cope with communication delays and update delays of some subsystems by applying a distributed asynchronous primal-dual (DAPD) algorithm. Furthermore, we propose an accelerated DAPD algorithm that accelerates the DAPD algorithm based on the work of Nesterov. The effectiveness of the proposed algorithms is illustrated through simulation results.